2020
DOI: 10.35229/jaes.764827
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and Seasonal Growth Estimates of the Black Goby, Gobius niger (Osteichthyes: Perciformes: Gobiidae) in the Southeastern Black Sea Region of Turkey

Abstract: Seasonal growth pattern and reproductive biology of the black goby, Gobius niger (n= 568; 2.1-14.6 cm TL), were monthly studied in southern Black Sea between December 2012 and November 2013. The seasonal von Bertalanffy growth parameters, computed from ELEFAN, were estimated as L∞= 11.9 cm TL, K= 0.701 year -1 , C= 0.633, and WP= 0.492 for the Hoenig seasonal model and as L∞= 12.1 cm TL, K= 0.680 year -1 for non-seasonal von Bertalanffy model. The size at sexual maturity (Lm) was estimated as 8.9 cm TL. The Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The average TL of females was significantly lower, due to the predominance of males in the higher length classes (Figure 2). In contrast, different populations have been described where there is no difference in TL between males and females of black goby (Kasapoğlu, 2016;Kırdar & İşmen, 2018;Bilgin & Onay, 2020). The L max of the black goby in the study area is close to that in previous studies in the Black Sea (Table 4).…”
Section: Size Classes (Cm)supporting
confidence: 76%
See 4 more Smart Citations
“…The average TL of females was significantly lower, due to the predominance of males in the higher length classes (Figure 2). In contrast, different populations have been described where there is no difference in TL between males and females of black goby (Kasapoğlu, 2016;Kırdar & İşmen, 2018;Bilgin & Onay, 2020). The L max of the black goby in the study area is close to that in previous studies in the Black Sea (Table 4).…”
Section: Size Classes (Cm)supporting
confidence: 76%
“…The sex ratio may differ from the theoretical ratio of 1:1 by size class and gender in the same population, being influenced by reproductive behavior, the adaptation of the population, environmental conditions, and food availability (Clarke, 1983). In other studies of Gobius niger in the Black Sea, females were found to predominate males (Kasapoğlu, 2016;Bilgin & Onay, 2020;Van & Gümüş, 2021). However, in this study we report more males.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations